Barriers and facilitators to pharmacy professionals' specialist public health roles: a mixed methods UK-wide pharmaceutical public health evidence review. (30th November 2022) - Ashiru-Oredope, D; Harrison, T; Wright, E; Osman, R; Narh, C; Okereke, U; Harvey, E; Bennie, M; Garland, C; Evans, A; Pyper, C
Abstract: Introduction: Pharmaceutical Public Health (PPH) is defined as "the application of pharmaceutical knowledge, skills and resources to the science and art of preventing disease, prolonging life, promoting, protecting and improving health for all through organised efforts of society". 1 In the UK (and globally) pharmacy professionals (PPs) contribute to the delivery of local and national public/population health (PH) interventions. 2, 3 However, little is known to what extent PPs have specialist/advanced roles within PH practice. Aim: The mixed methods review, commissioned by the UK Chief Pharmaceutical Officers in 2020, aimed to explore PPs' specialist PH contributions including barriers and opportunities. Methods: Databases available through PubMed were searched to retrieve articles published in English (2011- 2021) on seven topics including: emergency preparedness resilience and response (EPRR); integrating pharmacy to better support public health protection and improvement goals; public health skills and mitigating health inequalities. Two independent electronic surveys were developed, piloted and deployed for pharmacy and public health specialists via email cascade and social media. The surveys explored the extent to which PPs are involved in PH roles including the barriers and opportunities. Descriptive statistics summarised the data, and open-ended responses were themed. The NHS Health Research Authority tool identified this project did not require ethical approval as the surveys were service evaluation. Results: Rapid Evidence reviews: Following assessment of 2, 542 articles, 448 evidence statements were extracted from 135 relevant articles. They were predominantly from USA (39%) and UK (29%), with fewer high-quality reviews (17) or guidance (12), than moderate/low-quality reviews (42), single studies (33), or quantitative research (33). Common themes of PPs' contributions included: surveillance and intelligence gathering; advocacy for their communities; signposting; delivery of health improvement and protection services; supporting people with long-term-conditions; and EPRR. Barriers identified included: limited public and professional awareness of pharmacy's contribution to public health and under-resourced PH training. Pharmacy and PH professionals Surveys: There were UK-wide responses from 128 PPs and 37 PH specialists. Opportunities identified by PPs included: PH areas they directly contribute to (45%); qualifications, knowledge and skills (27%); strategic position in the community (19%), recent changing health landscape (4%). Barriers included lack of defined career pathway (20%); poor professional recognition (18%); limited resources (16%); lack of training and support (15%) and organisational and structural barriers (10%). PH specialists identified at least 12 areas from the Faculty of PH's functions and standards, they believed additional benefits would be realised by PPs working directly within PH teams. Although only 40% PH specialists had PPs working within their teams, 83% stated that it would be beneficial or very beneficial to have PPs specialising in PH. Discussion/Conclusion: Dedicated PPH training and system-wide leadership are required to fully realise population-level benefits. Low responses to the surveys present a study limitation, however, there was consensus from the themes emerging from both surveys and rapid evidence reviews findings. Pharmacy professionals make specialist contributions to PH despite barriers. Further investigation is required to identify how best to deploy advanced PPH resources. Future qualitative studies should be considered. References: 1. Walker, R. Pharmaceutical public health: the end of pharmaceutical care? The Pharmaceutical Journal 2000;264:340–1. 2. PHE (2017). Pharmacy: A Way Forward for Public Health https://www.gov.uk/government/publications/community-pharmacy-public-health-interventions (accessed 31 July 2021) 3. Thomson K, Hillier-Brown F, Walton N, Bilaj M, Bambra C, Todd A. The effects of community pharmacy-delivered public health interventions on population health and health inequalities: A review of reviews. Prev Med. 2019 Jul;124:98-109.